Blake's pouch cyst in children: Atypical clinical presentation. Issue 4 (August 2018) - Bontognali, Martina; Poretti, Andrea; Guzman, Raphael; Huisman, Thierry AGM; Ramelli, Gian Paolo
Blake's pouch cyst is a posterior fossa cystic malformation characterized by a infracerebellar cyst, absence of communication between the fourth ventricle and the subarachnoid space, and tetraventricular hydrocephalus. Children with Blake's pouch cyst typically present with macrocephaly due to hydrocephalus during the neonatal period or infancy. Atypical presentation is, however, possible. Here we present clinical and neuroimaging findings, as well as management and outcome, of an 18-month-old girl with atypical presentation of Blake's pouch cyst characterized by cerebellar ataxia. Familiarity with the neuroimaging findings of Blake's pouch cyst and differentiation between Blake's pouch cyst and other posterior fossa cystic malformations is important in terms of diagnosis, management, prognosis, and counseling of the affected families.